Intravenous cangrelor and oral ticagrelor as an alternative to clopidogrel in acute intervention. (15th May 2020) - Linfante, Italo; Ravipati, Kaushik; Starosciak, Amy Kathryn; Reyes, Dennys; Dabus, Guilherme
Abstract : Background: Dual antiplatelet therapy (DAP) is necessary to prevent thromboembolic events during carotid stenting, stent-assisted coil embolization, and implant of flow diverters (FD). However, DAP in the acute phase may be challenging. An intravenous alternative, cangrelor, has rapid onset, short plasma half-life, and more reliable antiplatelet action for acute interventions. The study objective was to evaluate feasibility and safety of IV cangrelor during acute neuroendovascular surgery procedures. Methods: We performed a retrospective analysis of our database of patients treated with stent-assisted coil embolization, FD placement for aneurysmal subarachnoid hemorrhage (aSAH), or stenting for acute internal carotid artery (ICA) occlusion where IV cangrelor was used. Morbidity, mortality, incidence of thromboembolic events, hemorrhages, and 90-day outcomes were reported. Results: Ten patients were found in our database from June 2018 through January 2019. Four patients had aSAH, four had middle cerebral artery strokes with tandem lesions, one had an ICA occlusion, and one had a vertebral artery aneurysm. One of the ten patients experienced a thrombotic event. One patient developed new post-procedural bleeding and two had worsening intracranial hemorrhage. Five patients were discharged home in stable condition, two to acute rehabilitation, one to a nursing facility, and two others expired (likely the result of the severe and evolving strokes). Of the eight who were discharged, six (75%) had a good 90-day functional outcome (modified Rankin Scale 0–2). Conclusion: Acute administration of IV cangrelor with or without oral ticagrelor is a feasible antiplatelet treatment option for acute neuroendovascular procedures.